HPTLC Analysis of the Antioxidant and Possible Antidiabetic Chlorogenic Acid in the in situ and in vitro Populations of the Low-calorie Sweetener Stevia rebaudiana (Bert.) Bertoni. Issue 6 (2nd November 2018) - , Shahnawaz; Pandey, Devendra Kumar; Dey, Abhijit
Abstract: Stevia rebaudiana (Bert.) Bertoni (Asteraceae), a native to South America and now well adapted and cultivated in different parts of India. Steviosides and extracts prepared from the leaves have been used widely all over the world as sweetening-agents, taste-modifiers and sugar-substitutes. Presently a study has been undertaken to analyze chlorogenic acid in the in situ and in vitro S. rebaudiana populations. Nodal explants were raised in Murashige and Skoog media supplemented 6-benzyladenine (BA; 8.5 mM) and indole- 3-butryic acid (IBA; 9.2 mM) to achieve the best shoot-yield. Chromatographic separation was performed on silica gel 60 F254 TLC plates with toluene: ethyl acetate: formic acid (5:5:1) as mobile phase. Densitometric measurement was performed in the ultraviolet region at λ=330 nm. In vitro raised S. rebaudiana from Jalandhar district was found to contain the maximum CGA (0.077%) content and in situ grown samples from the same district showed the minimun CGA content (0.021%) whereas in situ grown plant sample collected from Lucknow district possessed 0.010% of CGA. The present investigation not only quantifies the amount of CGA present in S. rebaudiana, it also presents a simple, validated and reproducible protocol to analyze CGA in plant samples using HPTLC.